Characteristics of Cationic Red X-GRL Adsorption by Diatomite Tailings - 郑仁基;高惠民;GUAN Junfang;REN Zijie;TIAN Jingjing (Journal of Wuhan University of Technology. Materials science edition, 2017)
As secondary mineral resources, diatomite tailings（DT） got from the Linjiang region of China were prepared and characterized by SEM, XRF and XRD. Mono-factor experiments were carried out to investigate the effects of the operation factor, including contact time, adsorbent concentration, initial p H value of the dye solutions, adsorption temperature and initial concentration of cationic Red X-GRL（X-GRL） on the adsorption of X-GRL. The adsorption kinetics, isotherms, thermodynamics and mechanisms for X-GRL were also studied. It was efficient for DT to adsorb X-GRL from aqueous solutions, and it was even discovered to have higher adsorptivity for X-GRL than diatomite concentrate（DC） in our previous test. The adsorption processes fit very well with the pseudo-second-order model and the Langmuir isotherm equation. In addition, various thermodynamic parameters, such as standard Gibbs free energy（ΔG°）, standard enthalpy（ΔH°） and standard entropy（ΔS°） have been calculated. From thermodynamic studies, it was seen that the adsorption was spontaneous and endothermic. The main driving forces of the physical adsorption on DT are electrostatic attraction. The reason why DT showed higher adsorptivity for X-GRL than DC was that there were more clay mineral particles within, which has a remarkable ability of dye adsorption due to its high surface area. DT as a cheap absorbent for X-GRL removal would replace or partially replace the activated carbon.